CAPITAL PUNISHMENT IN THE PERPECTIVE OF NON DEROGABLE RIGHTS - Noerdajasakti, Setiawan (Brawijaya Law Journal, 2016)
Capital punishment is still exist as one of kind punishments in Indonesia. The existence of capital punishment is based on the Penal Code and other laws. On the other hand, however, according to Constitution 1945, MPR Decree Number XVII/MPR/1988 on Human Rights and Law Number 39 / 1999 on Human Rights, the right to live cannot be limited under any circumstances (non derogable). Capital punishment and the right to live as the right that cannot be limited under any circumstances (non derogable) are contradictive. This contradiction results a conflict of norm between legislations that legalize the existence of capital punishment and legislations that legalize the existence of the right to live. Solutions should be resulted to solve the conflict of norms.